2022
DOI: 10.1002/jsfa.12348
|View full text |Cite
|
Sign up to set email alerts
|

Cucumis melo seed oil: agro‐food by‐product with natural anti‐hyperlipidemic potential

Abstract: BACKGROUND Sweet melon (Cucumis melo) seed is generally considered as agro‐waste, however, the current study aimed to use this waste as a valuable oil source. The seed oil extracted by two different extraction techniques (cold press and solvent extraction) was investigated for its anti‐hyperlipidemic potential. Hyperlipidemic rabbits were fed on the diet supplemented with sweet melon seed oil for 6 weeks (42 days) and thoroughly examined for the change in their lipid profile. RESULTS The blood lipid profile in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Shafi et al (2019) reported that the incorporation of more than 25% melon seed oil in yogurt negative impacted sensory properties and consumer acceptability. Other studies also reported the influence of “free” BFAs on the oxidative stability and sensory attributes of food products (Gulzar & Benjakul, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shafi et al (2019) reported that the incorporation of more than 25% melon seed oil in yogurt negative impacted sensory properties and consumer acceptability. Other studies also reported the influence of “free” BFAs on the oxidative stability and sensory attributes of food products (Gulzar & Benjakul, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These novel oil sources are commercialized in the nutraceutical and pharmaceutical markets in different dosage forms, including soft gels, gummies, capsules, and tablets Georges et al (2018). assessed the effects of administering krill oil or a placebo to young athletes for 6 weeks during a clinical trial and found that krill oil-supplemented athletes had higher levels of interleukin-2 production and natural killer cell cytotoxic activity 3 h postexercise, due to the PUFAs in the oil.3.6.1 | Impact of bioactive fatty acids on oxidative stability and sensory qualitiesShafi et al (2019) reported that the incorporation of more than 25% melon seed oil in yogurt negative impacted sensory properties and consumer acceptability. Other studies also reported the influence of "free" BFAs on the oxidative stability and sensory attributes of food products.…”
mentioning
confidence: 99%
“…The fatty acid pattern of melon seed oil is mainly characterized by the high content in linoleic acid (51–69%), with a proportion of saturated fatty acids lower than 15% [ 23 ]. This, together with the presence of other bioactive compounds such as sterols or tocopherols, make it a promising source of fat extracted from industrial waste that can be included in meat products to help to reduce the levels of cholesterol, as well as facilitate a consequent decrease in the development of atherosclerosis related to the incidence of coronary diseases [ 24 ]. On the other hand, pumpkin seed oil is also characterized by a high proportion of polyunsaturated fatty acids, ranging from 52.23 to 57.65% [ 25 ], where linoleic acid reaches over 44% and is a good source of other phyto-chemicals and bioactive compounds such as tocopherols, β-carotene, squalene and polyphenolic compounds [ 26 ].…”
Section: Introductionmentioning
confidence: 99%